STRENGTHENING TRANSFORMATIONAL LEADERSHIP AND PUBLIC POLICY INNOVATION IN INDONESIA - Berliana Mustika Rani (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
This study finds that transformational leadership plays a significant role in encouraging public policy innovation in Indonesia. This research is interesting because of its focus on transformational leadership as a driver of public policy innovation in Indonesia, which is relatively rarely studied in depth. This study uses a qualitative method that aims to explore a deep understanding of the phenomenon of transformational leadership and public policy innovation in Indonesia. Data collection was carried out through in-depth interviews with key informants and using data triangulation techniques. The results of the study show that transformational leadership plays an important role in encouraging public policy innovation in Indonesia. Transformational leaders are able to create a strong vision, motivate their subordinates, and encourage creativity and active participation in policy reform. Further research involving quantitative data and broader scope is needed to provide a deeper understanding of the effectiveness of transformational leadership in Indonesia.